IMPACT OF BEFORE AND AFTER JOINING SHGS ON SAVINGS, INVESTMENTS AND LEVEL OF KNOWLEDGE ON FINANCIAL LITERACY ANTECEDENTS - A STUDY W.R.T. BENGALURU URBAN DISTRICT (International Journal of Food and Nutritional Sciences, 2021)
Purpose : The main intention of presented paper is to know how far the socio economic characteristics of respondents impact on the study. Further, the study is conducted to the mode of savings of respondents before and after joining SHGs. Also the study conducted to probe the type of investments taken by respondents of Bengaluru Urban district. Since financial literacy assumes critical at present, the study also made a pragmatic attempt to know the level of financial literacy antecedents before and after joining SHGs.